Commodity Prices and Growth. (13th December 2017) - Ferraro, Domenico; Peretto, Pietro F.
Abstract: In this article, we propose an endogenous growth model of commodity‐rich economies in which: ( i ) long‐run (steady‐state) growth is endogenous and yet independent of commodity prices; ( ii ) commodity prices affect short‐run growth through transitional dynamics; and ( iii ) the status of net commodity importer/exporter is endogenous. We argue that these predictions are consistent with historical evidence from the 19th to the 21st century.